Mouse cortical organoids reveal key functions of p73 isoforms: TAp73 governs the establishment of the archetypical ventricular-like zones while DNp73 is central in the regulation of neural cell fate - Alonso-Olivares, Hugo; Marques, Margarita M.; Prieto-Colomina, Anna; López-Ferreras, Lorena; Martínez-García, Nicole; Vázquez-Jiménez, Alberto; Borrell, Victor; Marin, Maria C.; Fernandez-Alonso, Rosalia (Frontiers in Cell and Developmental Biology, 2024)
The process of neurogenesis is subjected to a tight spatiotemporal regulation, ensuring the correct development and organization of the central nervous system. Critical regulators of brain development and morphogenesis in mice include two members of the p53 family: p53 and p73. However, dissecting the in vivo function of these factors and their various isoforms specifically in brain development and morphogenesis is challenging, due to their pleiotropic effects. Here we addressed this challenge by developing an efficient and highly reproducible protocol to produce mouse brain organoids from pluripotent stem cells. These organoids contain neural progenitors and neurons, which organize into characteristic rosette-like structures that are structurally similar to the ventricular zone of the embryonic forebrain. Taking advantage of this new protocol, we generated mouse organoids from cells with full p73 deficiency. These organoids displayed increased neuronal apoptosis and decreased neural progenitor proliferation, linked to p53-compensatory activation, which accurately recapitulates previous in vivo observations in mice. Importantly, we further dissected the functions of individual p73 isoforms, finding that they establish a balance in neural progenitor cell biology. Our findings reveal a paradigm shift in the role of p73 regulating brain morphogenesis, with TAp73 being key in governing transcriptional programs essential for the establishment of the neurogenic niche structure, while DNp73 is central for a precise and timely regulation of neural cell fate.